Genome-wide Analysis of LBD (LATERAL ORGAN BOUNDARIES Domain) Gene Family in Brassica rapa - Huang,Xiaoyun (2018)
ABSTRACT LOB (lateral organ boundaries)-domain proteins deﬁne a family of plant-speciﬁc transcription factors involved in developmental process from embryogenesis to seed production. They play a crucial role in shaping the plant architecture through coordinating cell fate at meristem to organ boundaries. Identification of LBD genes from Brassica rapa genome, and analysis of phylogeny，gene structure, chromosome location, phylogenetic and tissue expression pattern analysis of LBD family genes in Chinese cabbage will be useful to the functions identification of plant LBD genes. Based on Brassica rapa genome database and bioinformatic method, Chinese cabbage LBD family genes were identified and the genes were sequenced. A phylogenetic tree was created using the MEGA5 program. Gene structure and chromosomes location were done by MapDraw, GSDS and Clustal X. Expression pattern of LBD genes at different development stages was analyzed based on RNA-seq. A total of 62 LBD genes were identiﬁed and could be classified into two classes and four subclasses according to the gene structure and conserved domain phylogeny relationship. Distribution mapping showed that the predicted LBDs were unevenly localized on all the 10 chromosomes, suggesting that they have an extensive distribution on the Brassica rapa chromosomes. Most of the LBD genes had differential expression pattern and showed highly diverse tissue-specific expression and functional diversity. To our knowledge, this is the ﬁrst report of a genome wide analysis of the Brassica rapa LBD gene family, which would provide valuable information for understanding the classiﬁcation and putative functions of the gene family.